Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Solve for n:
6n − 2(4n + 7) + 4 = -2
A:-6
B:-4
C:4
D:6


Sagot :

Answer:

B

Step-by-step explanation:

6n - 2(4n + 7) + 4= -2 firstly you open the bracket

6n - 8n - 14 + 2 = -2 then you collect the like terms

6n - 8n= -2 + 14 - 4 then add and subtract and divide by the coefficient

-2n= 12 - 4

-2n = 8

= n = 8 ÷ -2

n = -4

the answer is n = -4 i’m pretty sure